2014
DOI: 10.1074/jbc.m114.549592
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Follicle-stimulating Hormone Receptor as a Functional Trimer

Abstract: Background: A carbohydrate of follicle-stimulating hormone (FSH) has been proposed to sterically block other FSH molecules from binding to the putative receptor (FSHR) trimer.Results: FSH increases its receptor binding by 3-fold when the steric hindrance is removed.Conclusion: FSHR forms a functional trimer.Significance: This knowledge may improve designs of therapeutic drugs targeting FSHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 49 publications
6
86
0
Order By: Relevance
“…The trimerization was also observed in the crystals of LGR1 with FSH that was deglycosylated at Asn-52 in the ␣-chain (53). As the trimerization buried a large surface area of each protomer, the FSH-binding capacity of LGR1 was increased to 3-fold for the deglycosylated FSH (53).…”
Section: Divergence Of Ligand Recognition Bymentioning
confidence: 72%
See 1 more Smart Citation
“…The trimerization was also observed in the crystals of LGR1 with FSH that was deglycosylated at Asn-52 in the ␣-chain (53). As the trimerization buried a large surface area of each protomer, the FSH-binding capacity of LGR1 was increased to 3-fold for the deglycosylated FSH (53).…”
Section: Divergence Of Ligand Recognition Bymentioning
confidence: 72%
“…As the trimerization buried a large surface area of each protomer, the FSH-binding capacity of LGR1 was increased to 3-fold for the deglycosylated FSH (53). Although the trimer model of LGR1 in FSH recognition could well explain some observation in biochemical and functional studies (53), the in vivo relevance of the LGR1-FSH trimerization and the actual oligomerization form in living cells still need to be determined.…”
Section: Divergence Of Ligand Recognition Bymentioning
confidence: 99%
“…8A). However, FSHR has been reported to exist as dimers, trimers or small oligomers in the membrane (Guan et al, 2010, Jiang et al, 2014, Thomas et al, 2007). Accordingly, binding of FSH to one ligand binding site may affect FSH binding to a second ligand binding site, and dissociation studies seemed to provide supporting evidence (Urizar et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distal half of the ECD is linked to the TMD by a region of 130 amino acids known as the ‘hinge region’. A partial crystal structure of the ‘hinge region’ of the FSHR [12] along with other mutational studies on the TSHR hinge has now clearly shown that this structural bridge undergoes conformational changes in response to ligand binding and is involved in the activation of the receptor. Hence, this region is now often referred to as the ‘signal-specific domain’ [6,13].…”
Section: Structure and Function Of The Tshrmentioning
confidence: 99%